Molecular characterization of quinolones resistance determining region (QRDR) of Bartonella bacilliformis topoisomerasa IV in clinical isolates - Espinoza-Culupú, Abraham (2014)
Bartonella bacilliformis is the etiologic agent of Carrion's disease, which if endemic to Peru. Studies on antimicrobial resistance genes from clinical isolates of this pathogen are scarce, and the molecular characteristics of these genes and their region resistance-associated are currently unknown. In this work we made the molecular characterization of the quinolone-resistance, and establish the region (QRDR) for the topoisomerase IV, which is encoded by the parC and parE genes, as well as develop an antimicrobial susceptibility test for B. bacilliformis. 65 Blood samples from La Libertad, Cusco, Ancash and Piura were processed on Blood Agar plates and incubated at 30 °C, 5% CO2. The antimicrobial susceptibility was determined, then the genomic DNA extracted, aforementioned genes amplified, their sequence determined and it analyzed using bioinformatics tools. Six positive cultures were obtained. The isolates were susceptible to Ciprofloxacin (except one strain from Quillabamba – Cusco, which showed decreased susceptibility) and were resistant to Nalidixic Acid. From the sequence analysis of B. bacilliformis ParC and ParE there have been shown amino acid differences compared to the respective protein sequences from E. coli K12 MG1655, which is likely to confer resistance to Nalidixic Acid but not to Ciprofloxacin. It was determined that B. bacilliformis ParC and ParE proteins QRDRs are comprised between amino acids 67 to 118 and 473 to 530, respectively. The antibiogram and the minimal inhibitory concentration are best assessed using the #1 McFarland standards after a 6-day incubation period.